The Marketing Channels and Marketing Margins of Citronella Oil in Ogan Ilir District - Henny Malini; Erni Purbiyanti; Friska Syaiful (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2023)
Marketing is a spearhead of the sustainability of a business. In marketing, a strategy is needed to increase sales; in selling citronella essential oil, a strategy is needed to increase sales.  The problem citronella farmers face is the limited marketing area of citronella essential oil. In addition to the unstable prices, almost all citronella farmers in various regions of Indonesia are aware of the limited marketing area of citronella essential oil. Similar problems also occur among citronella farmers in Ogan Ilir District. Farmers face challenges accessing a wider market, and prices tend to decline yearly, causing volatility. This study aimed to analyze the marketing strategy of citronella essential oil, identify marketing channels, and calculate the marketing margin and Farmer's Share of citronella essential oil business actors. This research was conducted for one year, namely in 2022. The method used a case study.  The sampling method was purposive sampling, in which the samples taken were three self-help citronella distillation businesses used a purposive sampling method, and a sample of traders used snowball sampling. The study results on citronella essential oil business actors in Ogan Ilir District showed that the business actors carried out product, price, distribution, and promotion strategies. The marketing channel of farmers’ fragrant Essential Oil Lemongrass comprised three marketing channels, namely channel one consisting of a farmer-trader collecting- factory, channel two including farmer-trader retailer-consumer, and channel three composed of farmers-collecting traders-wholesalers-factories in Padang. Marketing channel 1 had a marketing margin of IDR 30,000/liter with a farmer's Share of 83.33%. Marketing channel 2 had a  marketing margin of IDR 250,000/liter, with a farmer's Share of 37.5%, and marketing channel 3 had a marketing margin of IDR 50,000, - with a farmer's Share of 75%. Marketing channel 1 was the most efficient.